“Ser Trabalhadora Produtiva é antes um azar”: a expansão da exploração capitalista sobre o trabalho reprodutivo - Marília Duarte de Souza (2020)
The relation of (un)productivity of reproductive work is a constant debate in feminism, since the issue of sexual division of labor and the performance of reproduction activities in a private sphere on the fringes of value production. - taken as the women's responsibility - are constantly related to female oppression. Thus, many debates are held regarding, on the one hand, the issue of the (un)productivity of this work in the capitalist relations of production and, on the other hand, the need for socialization, wage-earning or transfer of these activities to the productive sphere as an essential condition for the change in the relations of oppression experienced by women in the capitalist production system. That said, this paper aims to analyze the development of an economic sector which the work involved in the process of reproduction of the workforce is also a producer and creator of value, constituting exploitative relations based on oppressive relations that, at the same time, reinforces them. We also seek to analyze the theorie's limitations that explain the productive character of reproductive work in general as well as discuss the potentialities and limits of the transformation of reproductive work into productive work for a real emancipation of women. The data presented were collected by documentary analysis and secondary statistical data, and the analysis was performed from a historical materialistic perspective. We seek to apprehend and make reflections on the categories work, productive and unproductive work, reproductive work, oppression and exploitation. We conclude that the relations of oppression are engendered by and engender the relations of exploitation. Thus, the productive appropriation of reproductive labor does not necessarily mean a breakthrough for feminist struggle and women's emancipation, as it expresses yet another source of labor-force exploitation by capital, which allows the unique overcoming of some women's oppression in the daily reproduction of the life of workers, it does not surpass the condition of exploitation that engenders the universality of oppression under capitalism, according to the needs of value appreciation. Transforming this condition of exploitation into struggle for human emancipation is a task put to the working class whose horizon is to overcome any and all forms of oppression. We put, therefore, that the search for the real Emancipation of women, and even more for Human Emancipation, implies the search for overcoming the alienation of labor and the alienation between the sexes.